2017
DOI: 10.1007/s00216-017-0391-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass analytical method for the determination of natural/synthetic steroid hormones, phytoestrogens, and mycoestrogens in milk and yogurt

Abstract: Within this study, a new method enabling monitoring of various estrogenic substances potentially occurring in milk and dairy products was proposed. Groups of compounds fairly differing in physico-chemical properties and biological activity were analyzed: four natural estrogens, four synthetic estrogens, five mycoestrogens, and nine phytoestrogens. Since they may pass into milk mainly in glucuronated and sulfated forms, an enzymatic hydrolysis was involved prior to the extraction based on the QuEChERS methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Phytoestrogens can act as endocrine disruptors, impairing reproductive functions, generating temporal infertility, and potentially reducing the productive efficiency of dairy herds [ 9 , 28 , 29 , 30 , 31 ]. Interestingly, mycoestrogens (such as ZEN, alternariol (AOH), and their modified forms) and PEs (such as isoflavones) have synergistic effects [ 32 , 33 , 34 ], which must be considered in the context of a complete risk assessment on livestock reproductive performance [ 35 , 36 , 37 , 38 ]. Fungal and plant growth as well as concentrations of secondary metabolites in the dietary components and finally in the complete rations are influenced by multiple factors such as plant species/varieties, infecting/colonizing fungal species/varieties, climatic conditions, geography, parasitic/symbiotic interactions, use of pesticides, and other agricultural practices utilized [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytoestrogens can act as endocrine disruptors, impairing reproductive functions, generating temporal infertility, and potentially reducing the productive efficiency of dairy herds [ 9 , 28 , 29 , 30 , 31 ]. Interestingly, mycoestrogens (such as ZEN, alternariol (AOH), and their modified forms) and PEs (such as isoflavones) have synergistic effects [ 32 , 33 , 34 ], which must be considered in the context of a complete risk assessment on livestock reproductive performance [ 35 , 36 , 37 , 38 ]. Fungal and plant growth as well as concentrations of secondary metabolites in the dietary components and finally in the complete rations are influenced by multiple factors such as plant species/varieties, infecting/colonizing fungal species/varieties, climatic conditions, geography, parasitic/symbiotic interactions, use of pesticides, and other agricultural practices utilized [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…As it was indicated in the introduction section, only a few studies have been published regarding the evaluation of estrogenic compounds in milk or milk derivatives [6,7,[17][18][19][26][27][28][29] except for kefir samples, which has not been previously analyzed. Concerning cheese samples, it should be indicated that it has only been previously analyzed to determine phyto-, natural and synthetic estrogens, but not mycoestrogens [6,7,17,18].…”
Section: Comparison With Other Methodologiesmentioning
confidence: 99%
“…The mobile phase used for the analysis of phyto-and mycoestrogens consisted of MeOH (A) and water (B), while for natural and synthetic estrogens MeOH/ACN (50/50, v/v) (A) and 2 mM ammonium hydroxide (B) were used, based on a previous study [29]. The gradient applied was the same for all groups of analytes: 10% A with a flow rate of 0.3 mL/min (initial), 10-40% A (0.5 min), 99.9% A with an increase of the flow until 0.4 mL/min (7.5 min), 99.9% A (2 min), 10% A with a decrease of the flow to 0.3 mL/min (2 min), 10% A (2 min).…”
Section: Apparatus and Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…Negative effects of PEs on the reproduction of ruminants have been associated with pasture legumes such as clovers ( Trifolium spp) and lucerne/alfalfa ( Medicago sativa ) [ 27 ]. In the context of the reproductive performance of livestock, it seems important that co-occurrences of fungal metabolites and PEs are taken into consideration [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%